Depletion or over-expression of Sh3px1 results in dramatic changes in cell morphology. - Hicks, L.; Liu, G.; Ukken, F.P.; Lu, S.; Bollinger, K.E.; O'Connor-Giles, K.; Gonsalvez, G.B. (Biology open, 2015)
The mammalian Sorting Nexin 9 (Snx9) family consists of three paralogs: Snx9, Snx18 and Snx33. Most of the published literature to date has centered on the role of Snx9 in clathrin-mediated endocytosis (CME). Snx9 contains an Sh3 domain at its N-terminus and has been shown to interact with Dynamin and actin nucleation factors via this domain. In addition to the Sh3 domain, Snx9 also contains a C-terminal BAR domain. BAR domains are known to sense and/or induce membrane curvature. In addition to endocytosis, recent studies have implicated the Snx9 family in diverse processes such as autophagy, macropinocytosis, phagocytosis and mitosis. The Snx9 family is encoded by a single gene in Drosophila called sh3px1. In this report, we present our initial characterization of sh3px1. We found that depletion of Sh3px1 from Drosophila Schneider 2 (S2) cells resulted in defective lamellipodia formation. A similar phenotype has been reported upon depletion of Scar, the actin nucleation factor implicated in forming lamellipodia. In addition, we demonstrate that over-expression of Sh3px1 in S2 cells results in the formation of tubules as well as long protrusions. Formation of these structures required the C-terminal BAR domain as well as the adjacent Phox homology (PX) domain of Sh3px1. Furthermore, efficient protrusion formation by Sh3px1 required the actin nucleation factor Wasp. Tubules and protrusions were also generated upon over-expressing the mammalian orthologs Snx18 and Snx33 in S2 cells. By contrast, over-expressing Snx9 mostly induced long tubules.